Unlocking positive affect in public institutions: How daily recovery and micro-interruptions shape adaptive performance in the workplace - Junça Silva, A.; Caetano, A. (Journal of Public Affairs, 2025)
Based on the conservation of resources theory and the affective events theory, we have developed a framework to analyze how daily recovery enhances daily adaptive behaviors (adaptive performance), and how that improves daily positive affect. Moreover, we develop theoretical arguments for daily micro-interruptions as a boundary condition that buffers this relation and argue that the work context (i.e., telework, or at the office) can function as a protective factor. Using a diary design, our aim was to (1) explore the within-person effects of daily recovery on positive affect via adaptive performance, and (2) test the three-way interaction between daily micro-interruptions and the work context in the mediated relationship. We conducted a multilevel study in which 238 managers from public institutions participated. They filled out questionnaires at the end of the day for five consecutive working days (N = 238 × 5 = 1190). The results revealed that daily recovery positively influences employees' daily positive affect through their daily adaptive performance, but only on days with fewer daily micro-interruptions. They also showed that the employees' work context attenuates this interaction. Practical implications: this study provides insights into the role of daily micro-interruptions and their combined effect with the regimen of work practiced on that day. The findings deepen knowledge concerning how and when telework may be optimized, suggesting that telework is not always beneficial, nor detrimental, for performance: partially, it depends on the individuals' recovery and their daily micro-interruptions. We critically discuss the findings considering management practices that may allow employees to manage their daily life at work better, in particular, their recovery process and daily micro-interruptions.